Reflecting on the Development of the Decontamination Services: Pondering the Past, Presenting the Future. Issue 4 (April 2016) - Cobbold, A; Lord, S
This paper explores the historical developments of the UK decontamination services workforce over the past century. It will look back at how the services originated and look forward towards what the future could hold. This evolving workforce has progressed from traditional in-house training programmes towards accredited education, aiming to pave the way towards becoming a new profession – the healthcare scientist. The paper also explores some of the main drivers behind how previous healthcare professions have developed, and how these may impact on evolving professions such as decontamination services. The paper concludes by highlighting the importance of ensuring that staff are educated to national standards and keep abreast of current healthcare advances, in order to develop and retain the sterile services leaders of the future.